The Artifact Problem: A Category and Its Vicissitudes. (12th December 2022) - Preston, Beth
There is increasing interest in artifacts among philosophers. The leading edge is the metaphysics of artifacts and artifact kinds. However, an important question has been neglected. What is the status of the category 'artifact' itself? Dan Sperber (2007 ) argues against its theoretical usefulness for naturalistic social science. In Section 2, I lay out Sperber's argument, which is based on the observed continuum between natural objects and artifacts. In Section 3, I diagnose a fatal weakness affecting continuum-based arguments about categories. They fail to take into account recent thinking about classification in philosophy of science, which has been forced to accommodate continua in biology. In Section 4, I focus specifically on the species problem in philosophy of biology, and on pluralism about species concepts as a response to it. I then identify an analogous artifact problem, and argue that pluralism about artifact concepts is an appropriate response. In Section 5, I show that just as species pluralism leads to skepticism about the species category, so artifact pluralism leads to skepticism about the artifact category. Finally, in Section 6, I argue that Sperber's conclusion is correct—the artifact category is not theoretically useful, although not for the reasons he gives.